NUTRITIONAL PATTERNS AND NUTRITION OF AQUATIC ORGANISMS - Nurmatova Rukhsora Utkir kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The nutrition of hydrobionts can be autotrophic, heterotrophic and mixotrophic - when autotrophic organisms use ready-made organic matter to varying degrees (for example, many blue-greens). Among heterotrophs, a distinction is made between phagotrophs, which feed on living organisms or particles of organic matter, and saprophytes (osmotrophs), which absorb decay products of organic matter and metabolites of other organisms and feed primarily osmotically.